Life-Threatening Cardiac Manifestations of Pheochromocytoma - Luiz R. Leite; Paula G. Macedo; Simone N. Santos; Luiz Quaglia; Cezar E. Mesas; Angelo De Paola (Case Reports in Medicine)
Pheochromocytoma is a catecholamine-secreting tumor of the adrenal glands, usually with benign manifestations, whose typical clinical presentation includes the triad of headache, palpitations and diaphoresis. However, a wide range of signs and symptoms may be present. In the cardiovascular system, the most common signs are labile hypertension and sinus tachycardia. Systolic heart failure and ST-segment deviations mimicking myocardial infarction have also been reported, as well as QT interval prolongation and, rarely, ventricular tachycardia. We describe a challenging diagnosis of pheochromocytoma with many cardiovascular manifestations, which could have been missed due to the absence of typical symptoms.